2022
DOI: 10.28991/esj-2022-sied-010
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics and Mother Tongue Academic Achievement: A Machine Learning Approach

Abstract: Academic achievement is of great interest to education researchers and practitioners. Several academic achievement determinants have been described in the literature, mostly identified by analyzing primary (sample) data with classic statistical methods. Despite their superiority, only recently have machine learning methods started to be applied systematically in this context. However, even when this is the case, the ability to draw conclusions is greatly hampered by the "black-box" effect these methods entail.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…This is in line with the finding of Mupa & Chinooneka (2015) [6], who found that the high failure rate of students in grade seven schools in Zimbabwe is caused by instructors not using several types of teaching techniques, not preparing a variety of teaching and learning media, and limiting teachers' instructional materials to textbooks and curricula. This was also in line with the findings of Adamku (2022) [7], Muftah (2022) [8], Santiwatthanasiri (2018) [9], Hamad (2013) [10], Gardner & Lambert's (1972) theories and ideas [4], stating that the majority of students improved significantly when they were exposed to circumstances that gave them the chance to use communicative language engagement in cross-cultural communication, form bonds with foreign teachers and students, or explore personal or international interests [11]. As a result, the researcher established the following conceptual framework in Figure 1 for the investigation employing the aforementioned concept:…”
Section: -Conceptual Frameworksupporting
confidence: 89%
“…This is in line with the finding of Mupa & Chinooneka (2015) [6], who found that the high failure rate of students in grade seven schools in Zimbabwe is caused by instructors not using several types of teaching techniques, not preparing a variety of teaching and learning media, and limiting teachers' instructional materials to textbooks and curricula. This was also in line with the findings of Adamku (2022) [7], Muftah (2022) [8], Santiwatthanasiri (2018) [9], Hamad (2013) [10], Gardner & Lambert's (1972) theories and ideas [4], stating that the majority of students improved significantly when they were exposed to circumstances that gave them the chance to use communicative language engagement in cross-cultural communication, form bonds with foreign teachers and students, or explore personal or international interests [11]. As a result, the researcher established the following conceptual framework in Figure 1 for the investigation employing the aforementioned concept:…”
Section: -Conceptual Frameworksupporting
confidence: 89%
“…A Dataset of Real World Driving to Assess Driver Workload (HCILAB) [38] The dataset comprises around 2,500,000 ECG, skin conductance response (SCR), and body temperature samples, as well as a post-hoc video evaluation session of 10 drivers in a real-world motorway, highway, regular streets (50 km/h), and 30 km/h zone. The dataset was used to investigate the changes in drivers' mental workloads based on road conditions.…”
Section: Dataset Descriptionmentioning
confidence: 99%
“…Educational Data Mining identifies essential factors for academic success in a Portuguese business school's bachelor program, showing the influence of prior grades and school engagement on success at enrollment and the end of the first academic year [20,23]. The study by Nunes et al [24] combines machine learning efficiency with prototype analysis to quantify the impact of various factors on academic achievement in Mathematics and the mother tongue. Results highlight the significance of prior retention, legal guardian's education, and gender, offering insights for both research and practice.…”
Section: -Students' Modelingmentioning
confidence: 99%